Teaching Cognitive Biases in Clinical Decision Making: A Case-Based Discussion - Chew, Keng Sheng; van Merrienboer, Jeroen; Durning, Steven (https://www.mededportal.org, 2015)
This resource consists of five case scenarios aimed to teach/test participants in identifying the inherent cognitive biases as well as in considering alternative diagnoses (“thinking out of the box”). These cases are embedded with cognitive biases commonly encountered in the clinical setting. By using a blueprint to guide the creation of these cases, at least two or more aspects of patient care are tested (e.g. history taking, physical exam, data interpretation, diagnosis).